PITUITARY ADENOMA DUE TO PRIMARY HYPOTHYROIDIS AS A FACTOR OF MALE INFERTILITY - Kadirova Zarina Subxanovna (Western European Studies, 2024)
Infertility, defined as the inability to conceive after at least 1 year of unprotected sexual intercourse, affects about 15% of couples, and it is particularly common in developing countries [1,2,3]. Male and female partners alone are responsible for 20–30% of cases, respectively, but contribute to 50% of cases overall [1]. Several endocrine and metabolic diseases are involved in male infertility, such as hypogonadism, diabetes, obesity and adrenal dysfunction [7,8,9,10,11]. Beyond these conditions, thyroid dysfunction may affect male fertility too, albeit this is not widely investigated
Keywords: male; albeit; investigated; hypogonadism